Akupresure dan Yoga untuk Mengurangi Nyeri Haid (Disminore) pada Remaja Putri - Isni, Fitri; Salafas, Eti; Suryani, Lilis; Runiatin (Universitas Ngudi Waluyo, 2023)
Dysmenorrhea is menstruation accompanied by pain and 20-90% is often found in young women. In addition to pharmacological therapy in the form of non-steroidal anti-inflammatory drug therapy, dysmenorrhea can also be treated with non-pharmacological therapies such as acupressure and yoga.Acupressure is a safe non-pharmacological therapy to reduce dysmenorrhea pain and can be done independently. Another alternative in implementing non-pharmacological therapy is by doing yoga. Yoga therapy is one of the recommended relaxation techniques to reduce dysmenorrhea. Various problems that arise during menstruation are gynecological problems that are often complained of by adolescents, such as menstrual irregularities, menorrhagia, dysmenorrhea, and other related symptoms. The problem experienced by adolescent partners is the handling of dysmenorrhea other than medication. Based on the data obtained when conducting a pretest using a questionnaire, the lowest score in Semuntai Village was 35 and the highest was 80, in Sumi Village the lowest score is 45 and the highest is 75 and in Abola Village (Southeast Sulawesi) the lowest score is 30 and the highest is 80 ,young women do not know how to treat menstrual pain using acupressure and yoga methods. Therefore, acupressure and yoga counseling activities are carried out to treat menstrual pain in young women. The method used in this activity has 4 stages, namely determining respondents, filling out the pre-test, delivering material and evaluating. Respondents were 15 young women with 5 people in each region. The material presented uses booklets and demonstrations using videos. The result of community service activities that have been carried out in 3 different areas is an increase in knowledge of young women about acupressure and yoga to reduce menstrual pain before and after being given counseling. Abstrak Disminore adalah menstruasi yang disertai dengan rasa nyeri dan 20-90% sering ditemui pada remaja putri. Selain dengan terapi farmakologi yang berupa pemberian terapi obat anti inflamasi non steroid, disminore juga dapat diatasi dengan terapi nonfarmakologi seperti akupresure dan yoga. Akupresur merupakan terapi non farmakologi yang aman dilakukan untuk mengurangi nyeri dismenorea dan dapat dilakukan secara mandiri. Alternatif lain dalam pelaksanaan terapi non farmakologis yaitu dengan cara melakukan yoga. Terapi yoga merupakan salah satu teknik relaksasi yang dianjurkan untuk mengurangi tingkat dismenorea. Berbagai masalah yang timbul pada menstruasi merupakan masalah ginekologi yang sering dikeluhkan oleh remaja, seperti ketidakteraturan menstruasi, menoragia, dismenorea, dan gejala lain yang berhubungan. Permasalahan yang dialami mitra remaja adalah penanganan disminore selain dengan obat. Berdasarkan data yang diperoleh saat melakukan pretest menggunakan kuisioner menunjukkan nilai terendah di Desa Semuntai adalah 30 dan tertinggi 80, di Desa Sumi nilai terendah adalah 45 dan tertinggi 75 dan di Desa Abola (Sulawesi Tenggara) nilai terendah adalah 30 dan tertinggi 80 ,remaja putri belum mengetahui penanganan nyeri haid menggunakan metode akupresure dan yoga. Oleh karena itu, dilakukan kegiatan penyuluhan akupresur dan yoga untuk mengatasi nyeri haid pada remaja putri. Metode yang digunakan dalam kegiatan ini ada 4 tahap yaitu penentuan responden, pengisian pre test, penyampaian materi dan evaluasi. Responden adalah remaja putri berjumlah 15 orang dengan masing-masing wilayah 5 orang. Materi yang disampaikan menggunakan booklet dan demonstrasi menggunakan vidio. Hasil dari kegiatan pengabdian masyarakat yang telah dilakukan di 3 wilayah berbeda adalah adanya peningkatan pengetahuan remaja putri tentang akupresure dan yoga untuk mengurangi ny